Teams at the top : unleashing the potential of both teams and individual leaders - Katzenbach, Jon R., 1932- ([NetLibrary], 1998)
Teams at the Top shows how even the strongest and most successful CEO can improve the performance of various leadership groupings by enabling senior executives and next-level leaders to function as real teams as well as single-leader units - all without sacrificing each member's individual leadership capabilities and results. Teams at the Top explains how to recognize when a team effort at the upper management level is preferable and when a working group under single leadership fits best. Then, the book demonstrates how to develop the capability to shift into whichever mode is appropriate to the task at hand, integrating the discipline required for real teams with the discipline needed for executive leadership without compromising one in favor of the other.